(untitled) (CIPEEX, 2025)
The migratory process in Anápolis, as well as in the state of Goiás, is historically marked by national migration, also attracting international immigrants, whose integration into the Unified Health System (SUS) faces significant challenges. The objective of this study is to understand how the SUS and migratory flows in Anápolis relate to each other in terms of emerging challenges and the potential of the host language as a public policy. This is, therefore, a literature review based on databases, information systems, and official reports from the federal, state, and municipal governments, with the construction of an anamnesis instrument in Spanish and French aimed at welcoming immigrants. Although there are no specific data on the predominant nationalities in Anápolis, it is known that Goiás is home to mostly Venezuelans, Haitians, Colombians, and Bolivians. In addition, only 27.5% of municipal managers in Goiás recognize the existence of an immigrant population. Among the challenges, communication is the main obstacle to effective care for immigrants, especially due to the lack of intercultural mediators and public policies aimed at this need. There are 922 active immigrant registrations in the Basic Health Units of Anápolis, predominantly men and people between 20 and 59 years of age. Thus, there is a clear need for inclusive and culturally competent health policies in Goiás to ensure effective access to the SUS for immigrants, addressing language barriers and lack of information. These measures are essential to fully respect and integrate the rights of this population.